Experience of Norwegian Female BRCA1 and BRCA2 Mutation‐Carrying Participants in Educational Support Groups: a Qualitative Study. Issue 6 (19th April 2016) - Myklebust, Marion; Gjengedal, Eva; Strømsvik, Nina
Abstract: Women identified as BRCA1 and BRCA2 mutation carriers are advised to manage their cancer risk through intensive screening programs and/or by undergoing risk‐reducing surgery. The aim of this study was to explore and describe the experiences of female BRCA1/2 mutation carriers living with cancer risk and their experiences with participation in educational support groups (ESG). This qualitative study enrolled 17 (10 + 7) ESG participants in two different ESGs. The focus group interviews were performed immediately prior to and following two ESGs. The data were analyzed using John Knodel's (1993) practical approach. Three main themes were identified; the women's expectation and experience with ESG, the feeling of loneliness and isolation, and the feelings of living with "something else." In this paper we have focused on one of the main themes‐ the women's expectation and experience with ESG. This main theme presents four subthemes: the women's need for unambiguous, clear and unified information from health professionals, the need for social support, the important role of the patient representative, and increased knowledge potentially raising concern. Participation in an ESG for women with BRCA1 and BRCA2 mutations can provide relevant information and support in the decision‐making process related to risk‐reducing surgery.